2018
DOI: 10.17987/jcsm-cr.v3i1.48
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between hand grip strength and peak VO2 in community‐dwelling elderly outpatients

Abstract: Background Hand grip strength and peak oxygen uptake (VO 2 ) are important components of frailty. However, the relationship between these two variables among community-dwelling elderly people is still unclear. The present study aimed to investigate this relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…Additionally, we confirm grip strength to be significantly associated with lean mass, fat mass, CR fitness, BMD, A/G ratio, disease prevalence and physical activity levels. Such findings are consistent with previous studies, reporting associations between grip strength and lean mass [ 35 ], body fat % [ 35 ], BMD [ 36 , 37 ], peak oxygen uptake (VO2 peak ) [ 38 ] and morbidity [ 12 ]. While no previous research has explored the relationship between grip performance and A/G ratio, studies have demonstrated significant negative associations between grip strength and waist circumference [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, we confirm grip strength to be significantly associated with lean mass, fat mass, CR fitness, BMD, A/G ratio, disease prevalence and physical activity levels. Such findings are consistent with previous studies, reporting associations between grip strength and lean mass [ 35 ], body fat % [ 35 ], BMD [ 36 , 37 ], peak oxygen uptake (VO2 peak ) [ 38 ] and morbidity [ 12 ]. While no previous research has explored the relationship between grip performance and A/G ratio, studies have demonstrated significant negative associations between grip strength and waist circumference [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with previous reports demonstrating stronger associations between low grip strength, BMD and physical activity levels among females, compared to males [39,40]. While we found associations between low grip strength and disease prevalence in males only, and similar associations with CR fitness in females only, two recent studies have reported significant associations between these variables across both sexes [38,41]. Such inconsistencies are underscored by an overall lack of research relating to specific grip strength cutoff points and health.…”
Section: Screening Utility Of Grip Strengthsupporting
confidence: 91%
“…We have previously reported associations between peak VO 2 and SMI, and peak VO 2 and HGS, which we suggested might be underpinned by the degradation of sarcomeric proteins in both skeletal muscle and cardiomyocytes via the ubiquitin–proteasome system 38 39 . Coen et al .…”
Section: Discussionmentioning
confidence: 75%
“…We have shown that peak VO 2 is independently associated with age, Hb, physical function (SMI, HGS, & u‐WS), fatiguability, and CHF ( Table 4). Although relationships between peak VO 2 and indexes such as age, 1,36 anaemia, 37 SMI, 38 HGS, 39 u‐WS, 40 fatiguability, 41 and CHF 42 have previously been reported, no previous studies have investigated the relationship between peak VO 2 and this cluster of sarcopenia, frailty, and cachexia‐related factors.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, exercise tolerance was assessed using cardiopulmonary exercise testing. All of these assessments were evaluated as previously described 10,14–17 …”
Section: Methodsmentioning
confidence: 99%